Coniferyl ferulate alleviate xylene-caused hematopoietic stem and progenitor cell toxicity by Mgst2 - Yin, Zhao; Ou, Ruiming; Zhu, Yangmin; Liu, Zhi; Huang, Jing; Zhong, Qi; Li, Guangchao; Zhang, Qing; Liu, Shuang (Frontiers in Pharmacology, 2024)
Xylene exposure is known to induce toxicity in hematopoietic stem and progenitor cells (HSPCs), leading to bone marrow suppression and potential leukemogenesis.However, research on the gene expression profiles associated with xylene-induced toxicity in HSPCs, and effective therapeutic interventions, remains scarce. In our study, we employed single-cell RNA sequencing to capture the transcriptomic shifts within bone marrow HSPCs both prior to and following treatment with coniferyl ferulate (CF) in a mouse model of xylene-induced hematotoxicity. Subsequently, we pinpointed CF as a targeted agent using SPR-LC/MS analysis. This enabled us to confirm the link between the gene Mgst2 and specific cellular subtypes.Our data revealed that CF significantly countered the reduction of both monocyte and neutrophil progenitor cells, which are commonly affected by xylene toxicity. Through targeted analysis, we identified Mgst2 as a direct molecular target of CF. Notably, Mgst2 is preferentially expressed in neutrophil progenitor cells and is implicated in mitochondrial metabolic processes. By selectively inhibiting Mgst2 in bone marrow, we observed amelioration of xylene-induced hematotoxic effects.In summary, our findings suggest that coniferyl ferulate can mitigate the detrimental impact of xylene on hematopoietic stem and progenitor cells by targeting Mgst2, particularly within subpopulations of neutrophil progenitors. This discovery not only advances our comprehension of the cellular response of HSPCs to xenobiotic stressors like xylene but also identifies CF and Mgst2 as potential therapeutic targets for alleviating xylene-induced hematotoxicity.